2022
DOI: 10.1007/s11356-022-19691-0
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of toxicity and occurrence of degradation products of the fungicide tebuconazole after combined vacuum UV and UVC treatment of drinking water

Abstract: Antifungal azoles are the most frequently used fungicides worldwide and occur as active ingredients in many antifungal pharmaceuticals, biocides, and pesticides. Azole fungicides are frequent environmental contaminants and can affect the quality of surface waters, groundwater, and drinking water. This study examined the potential of combined vacuum UV (185 nm) and UVC (254 nm) irradiation (VUV/UVC) of the azole fungicide tebuconazole and the transformation product 1,2,4-trizole on degradation and changes in ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Tebuconazole is an azole fungicide used in vegetables, citrus, and field crops [ 162 ]. Moreover, it has high photochemical stability, very slow photodegradation, and slow microbial-mediated degradation in soil [ 163 , 164 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tebuconazole is an azole fungicide used in vegetables, citrus, and field crops [ 162 ]. Moreover, it has high photochemical stability, very slow photodegradation, and slow microbial-mediated degradation in soil [ 163 , 164 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it has high photochemical stability, very slow photodegradation, and slow microbial-mediated degradation in soil [ 163 , 164 ]. Tebuconazole was detected in drinking water and groundwater [ 162 , 165 ]. Tebuconazole exhibits moderate estrogenic activity [ 166 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of F. graminearum, a signicant increase in metabolic activity was observed aer irradiation, surpassing the control at all radiation doses. Other studies also report increased resistance of F. graminearum to UV radiation, [44][45][46] even compared to F. culmorum. 47 For A. niger and F. culmorum exposed to 90 min UV treatment, the relative metabolic activities increased to 50% and 15%, respectively (Fig.…”
Section: Effect Of Uv Radiation On Fungal Spores (Expressed By Metabo...mentioning
confidence: 90%
“…One of the most frequently used fungicide classes worldwide are azoles (imidazoles and triazoles), as they are the active ingredients in numerous pharmaceutical products and pesticides. They are recognized as environmental contaminants, and it has already been shown that they affect the quality of groundwater, surface waters and even drinking water [5]. The molecular properties of triazole fungicides used in agricultural practices reveal that they have low molecular weight and are moderately lipophilic, making them easily absorbable and persistent in sediments and organic surfaces in aquatic ecosystems [3,6].…”
Section: Introductionmentioning
confidence: 99%